Improved performance study of monolithic all perovskite tandem solar cell in nip and pin structure. (2022) - Kumar, Prashant; Shankar, Gyanendra; Pradhan, Basudev
Abstract: All perovskite tandem solar cell (APTSC) is among the most efficacious approach for fabricating high performance solar cell. In this paper, we have comparatively studied APTSC in nip and pin configuration. Performance of APTSC with FA0.8 Cs0.2 Pb(I0.7 Br0.3 )3 and (FASnI3 )0.6 (MAPbI3 )0.4 :Cl perovskite was simulated and improved by varying electron and hole transport layer for best output. Both the configuration was simulated and optimized on SCAPS-1D modelling software for best performance output. The device in pin configuration outperformed with PCE of 32.3 %, when compared with the device in nip configuration with the PCE of 31.82 %. This performance could be primarily attributed to the band alignment and number of layers in the device structure. All the photovoltaic parameters except fill factor was low in case of pin configuration. The work provides insight in understanding the device fabrication process in both the cases. This study would help us to understand and analyze the role of device configuration in photovoltaic cell.